Thematic Teaching Materials Using Science, Technology, Engineering and Mathematics Approaches to Improve Problems Solving Ability of Elementary School Students - Lestari, Titin; Nurhanurawati; Caswita; Yulianti, Dwi (LPPM Undiksha, 2023)
Thematic learning is expected that learning activities can involve students actively and in learning activities, so that students get direct experience which makes learning activities much more meaningful. Thematic teaching materials with the STEM approach are an alternative to improve students' problem-solving abilities. This study aims to analyze the validity, convenience, attractiveness, usefulness, and effectiveness of thematic teaching materials with the STEM approach to improve students' problem solving abilities in elementary schools. This research is a type of Research and Development (R&D) research, the development is carried out according to the theory of Borg & Gall. The subjects in this study were determined using a purposive sampling technique and obtained as many as 20 students. The data collection tool uses valid and reliable test instruments. Validity data analysis techniques show that thematic teaching materials with the STEM approach are very valid to use. Effectiveness data analysis technique uses N-Gain with a calculation result of 0.57 with a significance of 0.01<0.05. Based on this research, it can be concluded that the thematic teaching materials with the STEM approach developed are valid and effective for improving students' problem solving abilities in elementary schools.